Effects of Rare Earth Elements on the Generalist Herbivore, Melanoplus sanguinipes (Fabricius) (Orthoptera: Acrididae) - Allison, Jane (Université d'Ottawa / University of Ottawa, 2023)
The rare earth elements (REEs) are contaminants of emerging concern with environmental levels rising with increasing demand for these elements. REE pollution may arise from multiple sources. Increased extraction to meet the growing demand for emerging technologies will likely result in elevated environmental levels, due in part to mining waste, in part to industrial activity and in part to landfills holding discarded REE containing technologies. Monazite rocks, rich in REEs are commonly mined to produce phosphate-based fertilizers. Direct mining and fertilizer application are another substantial source of REE pollution. Despite growing environmental levels of REEs, the impact on organisms in terrestrial systems, where pollution originates, are poorly studied. Plants are known to accumulate REEs in root and shoot tissue through contaminated soils. Herbivorous species feeding directly on plant tissues with elevated levels of REEs may likewise accrue these metals in their body with unknown consequences for growth, development, reproduction, health, and survival. The goal of my thesis was to explore the risk posed by REE contamination to terrestrial invertebrates using Melanoplus sanguinipes (the lesser migratory grasshopper) as a model system. Two REEs of economic importance were selected for study, cerium (Ce) and neodymium (Nd). First, in chapter 2, I assessed if Melanoplus sanguinipes readily consumes REEs using high levels of contamination over a short exposure period to look for acute effects of consumption. Adults consumed both Ce and Nd indiscriminately with consequences for motor function when exposed to Ce and growth when exposed to Nd. REEs are persistent pollutants that may be underestimated by short exposure periods. In chapter 3, I set out to understand if living in a polluted environment (chronic exposure) would have negative impacts on survival and sublethal effects on growth, development, and reproduction. My results indicate that females carry high concentrations of Ce in their bodies while males carry higher levels of Nd. Overall survival was affected by exposure to Ce and a range of sublethal effects including delayed development, reduced adult mass and shortened adult lifespan (males exposed to Ce) were seen. In chapter 4, I investigated the possibility that accumulation of REEs in the body could impact energy stores (lipids, glycogen, free carbohydrates and protein), energy production (citrate synthase), affect redox balance, cause cellular damage (lipid peroxidase) and induce antioxidant (catalase) and biotransformation (glutathione-s-transferase) defenses. Energy production was increased at the lowest dose tested and slight declines in lipid stores were identified. However, these changes were not associated with an increase in detoxification processes, nor was there evidence of a loss of redox balance or cellular damage. Taken together, my thesis points to the need for both lethal and sublethal endpoints when characterising the risk of persistent pollutants.
Keywords: Rare earth elements; Grasshopper; Bioaccumulation; Growth and development; Body composition; Oxidative stress